THE PIGS’ BEHAVIOUR OF DIFFERENT GENOTUR - Булатович, О. М.; Гончар, В. І.; Шутяк, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The ethological observations relevant to solve commodity pig breeding and objectives: to identify adaptive characteristics of the organism and to explain some animals’ vital signs; stock explore reactions in different circumstances detention in terms of biologic evaluate the effectiveness of those or other systems;to conduct signifies our strong selection and selection of breeding animals in terms of inheritance respective life forms (preferably in an industrial pig farm) with quality assessment for a number of generations ethological reactions; interaction behavior of pigs to determine the types of higher nervous activity and a number of functional system body and to predict adaptive and pigs’ productive quality .Ethology pig production increases without any additional material costs, but only results rationalbehavior management, accounting and biological characteristics usage and animals’ physiological needs.